Effect of sweet potato flour of two local varieties on quality of breads (Journal of the Bangladesh Agricultural University, 2014)
The study was carried out in order to find out the effect of substitution of wheat flour with sweet potato flour of two local varieties (Local Sada and Local Lal) on the quality of bread. This study was also concerned with the analysis of proximate compositions of sweet potato and results showed that, fresh local sada and local lal sweet potato varieties contained moisture 70.10 and 66.78%; ash 4.46 and 4.21%; fat 0.71 and 0.74%; protein 1.75 and 1.63%; carbohydrate 22.98 and 26.64%; vitamin-C 8.86 and 9.49 mg/100g respectively. The compositions of sweet potato flour were also analyzed and showed that local sada and local lal sweet potato flour contained moisture 5.25 and 5.32%; ash 4.12 and 4.17%; fat 0.75 and 0.81%; protein 9.80 and 9.21%; carbohydrate 80.08 and 80.49%; vitamin-C 2.45 and 2.31 mg/100g respectively. This analysis showed that the sweet potato flour is quite rich in protein content. The breads containing of sweet potato flour were prepared using standard formulation with 5, 10 or 15% substitution of wheat flour by sweet potato flour and evaluated their acceptability by a number of panelists. The result obtained showed that the color, taste, texture, flavor and overall acceptability of the breads containing sweet potato flour were equally acceptable with control bread. Statistical analysis showed that the overall acceptability of bread with sweet potato flour was equally acceptable as the control bread and bread with 10% substitution level (local lal) was moderately acceptable and other products (including 15% substitution) were ranked as like slightly. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19929 J. Bangladesh Agril. Univ. 11(2): 301-306, 2013